Critical Water Depth and Installation Curves for Submarine Cable Deployment Process - Mamatsopoulos, Vasileios A.; Michailides, Constantine; Theotokoglou, Efstathios E.; Onoufriou, Toula (My University, 2020)
The purpose of the present paper is to propose installation curves for submarine cable deployment process for different water depths and tension deployment, emphasizing on the importance of modelling the “out of water” cable segment and the friction force between cable and overboard chute of the installation vessel. A custom-made analysis tool has been further expanded and used for the calculation of the cable hydraulic critical responses. Moreover, the concept of the critical water depth is proposed analytically for first time to define the cases in which the “out of water” cable segment can be ignored without denoting the accuracy of the minimum bending radius calculation. In addition, correction factors are proposed in relation to water depth and bottom tension values in order to eliminate the error of the safety factor calculation. Numerical formulation of the friction has been incorporated in the custom-made analysis tool as a further development. The analysis of various cable deployment cases proves that the inclusion of the “out of water” segment in the analysis is critical in shallow water areas. In contradiction, the modelling of the friction force is critical in deep water areas. However, both parameters are potential causes of important analysis errors.
Keywords: Marine cables; S-lay installation; Water depth effects; Catenary theory; Installation vessel; Critical water depth